The influence of thermal processing on the content of inorganic elements in snail meat - Danilova , I. S. (Scientific Progress & Innovations, 2019)
The purpose of the article was to investigate the content of inorganic elements in cooked meat of food species Helix pomatia, Helix aspersa maxima and Helix aspersa muller snails and to analyze the obtained results. Methods of the research. The content of inorganic elements was determined using X-ray fluorescence analysis in three replicates on the Spectroscan-MAX-G device of the Spectron RPA. The first reflection was the main parameter of the instrument for measuring spectral indicators. The value of the device step and the exposure time was 4. For this, 3 medium samples of boiled snail meat 20.0 ± 0.5 g of each species were taken. The meat was subjected to heat treatment for 90 minutes, because during this time the meat is considered to be ready for consumption. The research results. For the first time, not only in Ukraine, but also in the world, the influence of heat treatment on the amount of inorganic elements in the meat of Helix pomatia, Helix aspersa maxima, Helix aspersa muller, which are edible species and used as a delicacy, was studied. Snail meat is a source of 11 inorganic elements: strontium, bromine, selenium, zinc, cuprum, nickel, cobalt, ferrum, manganese, chromium, and calcium. Under the influence of high temperature, the amount of bromine, zinc, strontium, ferrum and manganese increased, and the amount of cuprum, cobalt decreased, while plumbum was not detected at all as compared with raw meat. Elements of scientific novelty. For the first time not only in Ukraine, but also in the world, we have studied the presence and number of inorganic elements in boiled meat of snails Helix pomatia, Helix aspersa maxima, Helix aspersa muller, which are food types and are used as a delicacy. Practical significance. Along with amino acid and vitamin compositions, we studied the question of inorganic elements’ composition in boiled snail meat. The obtained new data will be included in the methodical recommendations.